Digitally-enabled university incubation processes. (December 2022) - Chan, Yolande E.; Krishnamurthy, Rashmi; Sadreddin, Arman
Abstract: University business incubators are important drivers of entrepreneurial innovation ecosystems. The current study examines how digital tools—especially social, mobile, analytics and cloud (SMAC) technologies—facilitate internal and external interactions among university incubators and various actors in the entrepreneurial innovation ecosystem. This research uses a comparative study of multiple cases of Canadian university incubators in a longitudinal manner to explore the role of these digital technologies in the three primary incubation process activities: incubatee search and selection, business support, and networking. Findings suggest SMAC technologies are important for facilitating the incubation processes of university incubators but are currently underutilized. Digital technologies can be used further to help incubator managers and entrepreneurs develop innovative ideas, foster incubatees, and contribute to entrepreneurial ecosystems. Highlights: This study examines how digital technologies facilitate incubation process components to improve the effectiveness of university incubators. We highlight incubators' use of SMAC technologies for internal processes - to select incubatees and provide services. We show how incubatees can use simple, readily available digital technologies to develop and grow their businesses. We focus on how university incubators leverage SMAC technologies to connect incubatees with entrepreneurial ecosystems.